GaAs Photovoltaics: Microtransfer Printing High‐Efficiency GaAs Photovoltaic Cells onto Silicon for Wireless Power Applications (Adv. Mater. Technol. 8/2020). Issue 8 (10th August 2020) - Mathews, Ian; Quinn, David; Justice, John; Gocalinska, Agnieszka; Pelucchi, Emanuele; Loi, Ruggero; O'Callaghan, James; Corbett, Brian
Abstract : The use of micro‐transfer printing presents a huge opportunity to decrease the cost of fabricating self‐powered sensors, by enabling heterogeneous integration of III‐V devices at the foundry wafer level. In article number 2000048, Brian Corbett and co‐workers demonstrate a GaAs laser power converter integrated on silicon, for power‐over‐fiber applications, with an efficiency of ≈50% under high intensity optical illumination.